Dual-stage optimizer for systematic overestimation adjustment applied to multi-objective genetic algorithms for biomarker selection - Cattelani, Luca; Fortino, Vittorio (Briefings in bioinformatics, 2024)
The selection of biomarker panels in omics data, challenged by numerous molecular features and limited samples, often requires the use of machine learning methods paired with wrapper feature selection techniques, like genetic algorithms. They test various feature sets—potential biomarker solutions—to fine-tune a machine learning model’s performance for supervised tasks, such as classifying cancer subtypes. This optimization process is undertaken using validation sets to evaluate and identify the most effective feature combinations. Evaluations have performance estimation error, measurable as discrepancy between validation and test set performance, and when the selection involves many models the best ones are almost certainly overestimated. This issue is also relevant in a multi-objective feature selection process where various characteristics of the biomarker panels are optimized, such as predictive performances and feature set size. Methods have been proposed to reduce the overestimation after a model has already been selected in single-objective problems, but no algorithm existed capable of reducing the overestimation during the optimization, improving model selection, or applied in the more general multi-objective domain. We propose Dual-stage Optimizer for Systematic overestimation Adjustment in Multi-Objective problems (DOSA-MO), a novel multi-objective optimization wrapper algorithm that learns how the original estimation, its variance, and the feature set size of the solutions predict the overestimation. DOSA-MO adjusts the expectation of the performance during the optimization, improving the composition of the solution set. We verify that DOSA-MO improves the performance of a state-of-the-art genetic algorithm on left-out or external sample sets, when predicting cancer subtypes and/or patient overall survival, using three transcriptomics datasets for kidney and breast cancer.